Outdoor play opportunities for children with additional needs in Early Learning and Care Settings in Ireland - Mooney, Sylvia (Trinity College (Dublin, Ireland). School of Education, 2020)
This research study was inspired by childrens rights. All children have the right to play and to participate (UN, 1989; UN, 2006). Qualitative research was employed throughout this study to explore the outdoor play opportunities of children with additional needs in ELCS in Ireland. The current study incorporated three settings and focused on eight children with additional needs and ten ELC professionals (ELCP), to explore the topic of outdoor play opportunities for children with additional needs, from the perspectives of both children and professionals. The research examined how children with additional needs perceive outdoor play spaces and activities, how outdoor play influences children’s development and if children with additional needs enjoy the same outdoor play opportunities as their typically developing peers. The study established that outdoor play enhanced the holistic development of children with additional needs. Findings of the current study established that children developed fundamental skills and positive dispositions by engaging in outdoor play experiences. Indeed, social and emotional competencies were enhanced as participating children engaged in significantly more positive peer interactions during outdoor play, thus, supporting the development of peer relationships, self-regulation, social acceptance, independence, self-esteem and well-being. Barriers to children’s participation in outdoor play were also highlighted throughout this study. Changes to policy and practice are required to eliminate these barriers so that all children can reach their potential regardless of their individual needs and abilities (Besio & Stancheva-Popkostadinova, 2018). Increased government investment is required to reduce the current child to adult ratio requirements and to support professionals to engage in continuous professional development to deepen their knowledge and provide meaningful play experiences for children. This current study highlights the correlation between outdoor play and well-being and suggests that children with additional needs enjoy outdoor play experiences. Further research on a larger scale is required to explore, incorporate and prioritise the voices of children with additional needs in future policy and practice and to empower all children to exercise their rights.
Keywords: Education; Early Intervention